Association between dietary carbohydrate quality index, obesity markers and mammographic findings in women treated by the Brazilian public health system - Mendes, Ana Luiza de Rezende Ferreira; Sampaio, Helena Alves de Carvalho; Carioca, Antônio Augusto Ferreira; Pinheiro, Luiz Gonzaga Porto; Vasques, Paulo Henrique Diogenes; Rocha, Daianne Cristina; Cacau, Leandro Teixeira; Meneses, Ayana Florencio de; Bezerra, Ilana Nogueira (Seven Editora, 2024)
Obesity is a risk factor for breast cancer and diet can be a risk factor for this disease as well as contributing to overweight. Dietary carbohydrates are always under discussion as to potential harms in this context. There are no studies that identify obesity and dietary carbohydrates in relation to alterations present in mammographic examinations. The aim of this study was to evaluate whether there is an association between mammographic findings, carbohydrate quality index (IQC) and obesity. Methodology: The sample consisted of 620 women stratified according to the BreastImaging Reporting and Data System (BI-RADS) into two groups: and with abnormal mammographic findings. The following obesity markers were used: Body Mass Index, Waist Circumference, Waist/Hip Ratio, Waist/Height Ratio, A Body Shape Index, Body Roundness Index and Body Fat Percentage, the latter defined by ultrasound. The IQR was determined from two 24-hour food recalls and was composed of the following components: fiber, glycemic index, whole grain/total grain ratio, and solid/total carbohydrate ratio. Results: There were 219 (35.3%) women with abnormal mammographic findings. There was no difference between the two groups of women considering markers of obesity, except for waist circumference, with greater accumulation of abdominal fat among women with altered mammographic findings. There was no difference between the groups considering IQC and markers of obesity. Conclusion: In the group of women evaluated, there was no association between mammographic findings, obesity and carbohydrate quality index. Women with abnormal mammographic findings exhibit greater accumulation of abdominal fat, estimated by the waist circumference indicator. DOI:https://doi.org/10.56238/sevened2024.010-018